EGILS consensus report. Gastric extranodal marginal zone B-cell lymphoma of MALT. Issue 6 (11th February 2011) - Ruskoné-Fourmestraux, A; Fischbach, W; Aleman, B M P; Boot, H; Du, M Q; Megraud, F; Montalban, C; Raderer, M; Savio, A; Wotherspoon, A; ,
Abstract : This consensus report of the EGILS (European Gastro-Intestinal Lymphoma Study) group includes recommendations on the management of gastric extranodal marginal zone B-cell lymphoma of MALT. They are based on data from the literature and on intensive discussions and votings of the experts during their annual meetings.